Penerapan Teori Deming untuk Meningkatkan Manajemen Mutu di Perpustakaan - Asnah Yuliana (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2018)
Library can serve as a vehicle for education, research, conservation, information, and recreation to improve the intelligence and empowerment of the nation. The policy to advance the library world in Indonesia is considered the most realistic option as a lifelong learning vehicle to develop the potential of the community to become a human being who believes and cautious to God Almighty, having noble character, healthy, knowledgeable, capable, creative, independent, and citizen a democratic country and responsible for supporting the implementation of national education. However, the development of the library as the center of the development of science is constrained by the quality management in the library that has not been able to reach the maximum level. The problem boils down to one major problem ie the lack of a quality assurance system in the library that becomes the driving spirit in order to realize the maximum library development. The above mentioned problems can be solved if a library has a good quality management system. After the authors searched the literature on library quality management systems, the authors found only one quality management used in Indonesia that is ISO 9001: 2008. This paper will discuss more about library development using quality management initiated by Edward Deming, because it focuses on the customer or library users using the 14 principles that have been formulated.